Two new species of lizards of the genus Stenocercus (Iguania, Tropiduridae) from central Peru - Köhler, Gunther; Lehr, Edgar (Zootaxa, 2015)
We describe two new species of Stenocercus from the Andes of central Peru (Departamento Ancash): Stenocercus amydrorhytus sp. nov. from elevations between 2810 and 3075 m and S. johaberfellneri sp. nov. from elevations between 3120 and 3200 m. Stenocercus amydrorhytus is most similar to S. ivitus, S. chrysopygus, S. melanopygus, S. modestus, S. orientalis, and S. stigmosus from which it differs in having a combination of 44–52 vertebral scales, 42–47 scales around midbody, 18–21 gulars, and 23–26 subdigital lamellae under fourth toe, the lateral nuchals less than half the size of dorsal nuchals, predominantly smooth dorsal head scales, a poorly developed oblique neck fold with a shallow or no mite pocket underneath, a uniformly gray venter in preservative in the only known adult male, and a tail length less than 70% of total length. Stenocercus johaberfellneri is most similar to S. latebrosus and S. ornatissimus from which it differs in having a combination of 47–53 vertebral scales, 46–53 scales around midbody, the presence of a postfemoral pocket in adult males, a throat pattern of bold black streaks or reticulations in adult males, a dusky or grayish venter in preservative without black spots or reticulations, and lateral nuchals less than half the size of dorsal ones.